Pengelolaan Supervisi Akademik di SMA Negeri Punung Kabupaten Pacitan - Setyawan, Dwi Agus (2016)
Regulation of the Minister of national education no. 13 of 2007 about the standard principal/madrasa, one of which is the kompentensi supervision in order to develop improved education. This study had two purposes. (1) Mendiskripsikan the implementation of academic supervision towards teaching and learning activities in SMA Negeri Punung, and (2) Mendiskripsikan the implications of implementing academic supervision towards the teaching and learning activities in SMA Negeri Punung. This research uses ethnographic approach. The place of research in SMA Negeri Punung. Interviewees include the principal, vice principal and teacher. Data collection using observation, interviews, and documentation. Data validity was tested by using triangulation. Technical analysis by reduction of data, data and cereal verification. as well as the withdrawal of the conclusion. There are two findings of research results. (1) the academic supervision of the implementation of the principal: a) the academic supervision of the implementation Process is done with three stages, the stages of preparation, implementation and follow-up/assessment; b) Style used democratic styles; c) techniques/methods use direct and indirect; d) Problem faced by students, teachers, parents and principals. (2) the implications: a) the level of readiness of the school; b) Presepsi the citizens its main very positive school teachers toward professionalism and; c) success (benchmarks) that was reached after the academic supervision of repair is physically better.